Selected Aspects of Non-Profit Organisations - Horvat, Tatjana (IntechOpen, 2020)
The volatility of the economy, political instability, and greater demands on not-for-profit organisations (non-profits) will require considerable rethinking and refocusing for many organisations. These days, non-profits evolve while attempting to regain financial ground, focusing more on workflow, fundraising, and staffing. The book highlights the upcoming challenges, among others funding instability, with a continuing shift in funding with more grantors focusing on funding mobilisation instead of intervention. Another challenge is clustering, which is where organisations are more likely to band together with others to share overhead costs, resources, and personnel. The non-profit sector will undergo essential integrations where the free flow of data and information will be crucial. Non-profits will continue to adjust their goals and priorities to meet changing trends. While the top priority was once acquiring new donors, that has now been eclipsed by the need for non-profits to engage the community and promote general brand awareness.